I Want to Be a Billionaire: How Do Extrinsic and Intrinsic Values Influence Youngsters' Well-Being?. Issue 1 (March 2019) - Van Den Broeck, Anja; Schreurs, Bert; Proost, Karin; Vanderstukken, Arne; Vansteenkiste, Maarten
Values guide our attitudes and behavior, but to what extent and how do individual values determine our overall well-being? Self-determination theory holds that particular types of values (i.e., intrinsic or extrinsic) matter most, but the person-environment fit perspective argues that any values can be beneficial as long as they align with values prevalent in one's environment. The evidentiary support for these competing claims is inconclusive. We use the World Value Survey to see how these perspectives do in predicting life satisfaction, happiness, and health in youngsters aged 18 to 30 around the world. Our results generally confirm hypotheses derived from self-determination theory, showing that the type of values held by youngsters and the type of values prevailing in their environments account for significant variation in young peoples' life satisfaction, happiness, and health. The pattern of evidence suggests that youngsters benefit from attaching greater importance to intrinsic values related to affiliation and community contribution rather than to extrinsic values that relate to financial success and accumulation of power.